2015
DOI: 10.1159/000441518
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Clinical, Placental Histology and Microbiological Findings in Spontaneous Preterm Births

Abstract: Aims: To examine the occurrence of chorioamnionitis and abruption among women who had a spontaneous preterm birth (SPTB), the correlation between clinical and placental findings, and the impact of these complications on neonatal outcome after delivery. Methods: This was a retrospective case-control study conducted between 2008 and 2012 at a single teaching hospital. The study group included all women who had an SPTB (23-36 weeks).Placentas were cultured and underwent histological examination. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Placental abruption has been shown by other studies to be nine times more likely to occur in preterm gestational ages than is in term gestational ages (2.8% versus 0.3%, respectively) [ 29 ]. Still, other studies have shown that placental abruption implicates itself in 5.8% of births occurring before 35 weeks of gestation, with another finding that 50% of women with PTB had “clinical or histological abruption, chorioamnionitis, or both” [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Placental abruption has been shown by other studies to be nine times more likely to occur in preterm gestational ages than is in term gestational ages (2.8% versus 0.3%, respectively) [ 29 ]. Still, other studies have shown that placental abruption implicates itself in 5.8% of births occurring before 35 weeks of gestation, with another finding that 50% of women with PTB had “clinical or histological abruption, chorioamnionitis, or both” [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that bacterial infections are the cause of PPROM and preterm labor (59)(60)(61). However, until 2014, it was thought that the placenta did not contain its own microbiome.…”
Section: Placental Microbiome?mentioning
confidence: 99%
“…The placenta has typically been viewed as a sterile organ (5). Yet, it has long been known that bacterial infection of the placental amnion and chorion (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and/or villous tree (15,18,(25)(26)(27) is associated with preterm labor (16,18,(28)(29)(30)(31)(32)(33)(34), preterm prelabor rupture of the membranes (PPROM) (18,29,30,35,36), histological chorioamnionitis (15-17, 22, 23, 37, 38), clinical chorioamnionitis (15,(36)(37)(38)(39)(40)(41)(42), and congenital infection (26,(43)(44)(45)(46)(47). What is unique about many recent investigations is that they further report detection of a microbiota in placentas from uncomplicated pregnancies at term (1,…”
Section: Introductionmentioning
confidence: 99%